1999
DOI: 10.1046/j.1442-2042.1999.06441.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognostic factors related to primary superficial bladder cancer tumor recurrence in prophylactic intravesical epirubicin therapy

Abstract: Purpose: The aims of the present study were to examine the effects of intravesical instillation of epirubicin on tumor recurrence and to identify tumors that are at a high risk of recurrence. Methods: Forty-five patients with primary superficial bladder cancer were treated with prophylactic intravesical epirubicin following transurethral resection of the bladder tumor (TUR-BT). Epirubicin (20 mg) was administered intravesically every second week for 4 months and then once a month or every 2 weeks for next 8 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 72 included studies, five included only Ta NMIBC patients [12–16], and 26 studies included only T1 NMIBC patients [17–42]. The other 41 studies included both Ta and T1 patients [43–83].…”
Section: Resultsmentioning
confidence: 99%
“…LCA5L (A_16_P03587947) encoding the ligand of LCA5 has been widely reported to participate in centrosomal or ciliary functions according to recent publications [ 76 , 77 ]. Additionally, the interaction between LCA5L and NDK1 has been confirmed to contribute to the pathogenesis of DS with specific CNVs [ 78 , 79 , 80 ]. Although no direct evidence revealed the specific contribution of LCA5L in patients with DS, a study [ 81 ] on the congenital heart defects confirmed that copy number variation of LCA5L also participated in the pathogenesis of congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…El análisis descriptivo de ambas series revela que el porcentajes de recidiva en ambas centros (48.8% y 56.6%) es similar al de otras series históricas publicadas [10][11][12][13][14][15][16], sin embargo el porcentaje de progresión es menor que en otros estudios [1, 14,[16][17][18] Los factores pronósticos para una primera recidiva son equivalentes al de otras series e incluyen la edad, grado, número y tamaño tumoral junto con el tratamiento. Tanto la presencia de cis como el estadio tumoral, no fueron significativos para la recidiva tumoral [17].…”
Section: Discussionunclassified